Large Cardamom Farming in Some Villages of Ilam District - Subedi, Bhim prasad (Himalayan Review, 2011)
Not available. Key words: Cardamom Farming; International trade; Ilam District; Nepal The Himalayan Review Vol. 14, 1982 Page: 25-27 Uploaded Date: April 10, 2011